Theatre in urban regeneration : global cities, new narratives and the regeneration of Ballymun (1998-2010) - Malone, Niamh (Trinity College (Dublin, Ireland). School of Education, 2011)
This study examines the role of community theatre within an urban community undergoing regeneration at the beginning of the 21st century. The current phase of globalisation has prompted reconsideration of the meaning and legitimacy of social networks which are commonly taken to constitute ‘community’. Pressures from the impact of globalisation have urged scholars to redefine what community actually means, and to question the suitability of contemporary rhetoric, organised around a dichotomy of communities of location and communities of ideology. One of the most evident and direct consequences of globalisation in the western world is the pursuit by cities of global status (Sassen, 2001). This pursuit has created an era of widespread urban regeneration, and the role played by the arts and culture in supporting such endeavours is a central focus of this research.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin